PERILAKU MASYARAKAT PETANI DALAM PENGELOLAAN LINGKUNGAN DIKAWASAN HULU DAERAH ALIRAN SUNGAI BATANG KURANJI - aslansari aslansari (Jurnal Embrio, 2018)
The behavior of farmers in environment management in the upstream region is strongly influenced by reciprocal relationship between human and environment. Based on law No.23 in 1997 about environment management, article 5 explain that everyone has rights to role in environment management and duty to protect environment conservation. A ware that reciprocal relationship between human and environment to protect environment as for as stream flow (DAS) and it still continue needs human demanded form wise measure who lives around steam flow for human matrealized as environment builder and control resources advantage on wise. This research was did in upper course of river, center and down stream Batang Kuranji consist of Lambung Bukit village. This research was did with short survey, data raising method include primer and secondary data. Data analys was used measuring community behavior which did with quantitative method, double regression analys and continue F-test (varian analys) also t-test (partial analys). The result of research was showed that community behavior in environment management belong to medium and not good which include farming activity. While factors are influence behavior consist of understanding high environment, low category of government commitment and kind of work category with realm connected.